Experimental investigation on angle cleat connections for cold-formed steel sections - Tan, Cher Siang (2011)
The application of cold-formed steel in light steel framing design can become a popular choice of Industrialized Building System (IBS), by extending the steelwork design into residential housing. However there is a lack of in-depth study on the joints behaviour for primary structures, particularly the beam-to-column connection. This paper presents the isolated joint test on three types of connection using steel angles, namely web-cleats, top-seat flange-cleats and combined flange-web-cleats connections. Six specimens with different joint configuration and thickness of cleat were tested. The experimental setup, procedures and failure modes of the joints are discussed in detail. From the comparison, it is observed that by increasing the angle-cleat size from 2 mm to 6 mm, the moment resistance would increase in the range of 2.00 to 2.37. The ratio of difference for rotational stiffness increases in the range of 2.05 to 2.26.